Acetylsalicylic acid interferes with embryonic kidney growth and development by a prostaglandin-independent mechanism - Welham, Simon J.M.; Sparrow, Alexander J.; Gardner, David S.; Elmes, Matthew J. (Baishideng Publishing Group Inc, 2017)
AIM: To evaluate the effects of the non-selective, non-steroidal anti-inflammatory drug (NSAID) acetylsalicylic acid (ASA), on ex vivo embryonic kidney growth and development. METHODS: Pairs of fetal mouse kidneys at embryonic day 12.5 were cultured ex vivo in increasing concentrations of ASA (0.04-0.4 mg/mL) for up to 7 d. One organ from each pair was grown in control media and was used as the internal control for the experimental contralateral organ. In some experiments, organs were treated with ASA for 48 h and then transferred either to control media alone or control media containing 10 μmol/L prostaglandin E2 (PGE2) for a further 5 d. Fetal kidneys were additionally obtained from prostaglandin synthase 2 homozygous null or heterozygous (PTGS2-/- and PTGS2-/+) embryos and grown in culture. Kidney cross-sectional area was used to determine treatment effects on kidney growth. Whole-mount labelling to fluorescently detect laminin enabled crude determination of epithelial branching using confocal microscopy. RESULTS: Increasing ASA concentration (0.1, 0.2 and 0.4 mg/mL) significantly inhibited metanephric growth (P < 0.05). After 7 d of culture, exposure to 0.2 mg/mL and 0.4 mg/mL reduced organ size to 53% and 23% of control organ size respectively (P < 0.01). Addition of 10 μmol/L PGE2 to culture media after exposure to 0.2 mg/mL ASA for 48 h resulted in a return of growth area to control levels. Application of control media alone after cessation of ASA exposure showed no benefit on kidney growth. Despite the apparent recovery of growth area with 10 μmol/L PGE2, no obvious renal tubular structures were formed. The number of epithelial tips generated after 48 h exposure to ASA was reduced by 40% (0.2 mg/mL; P < 0.05) and 47% (0.4 mg/mL; P < 0.01). Finally, growth of PTGS2-/- and PTGS2+/- kidneys in organ culture showed no differences, indicating that PTGS2 derived PGE2 may at best have a minor role. CONCLUSION: ASA reduces early renal growth and development but the role of prostaglandins in this may be minor.